2022
DOI: 10.1177/19322968221106194
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Requirements for Basal and Auto-Correction Insulin Delivery in Advanced Hybrid Closed-Loop System: 4193 Days’ Real-World Data of Children in Two Different Age Groups

Abstract: Background: The insulin requirements of people with type 1 diabetes (T1D) can vary throughout the day due to factors such as biorhythm, exercise, and food intake. The MiniMed 780G system delivers micro boluses to adjust basal insulin and delivers auto-correction boluses to meet insulin needs when micro bolus increases are insufficient. Through analysis of MiniMed 780G data, this study investigates the variations in insulin requirements throughout the day. Methods: 4193 days’ pump and continuous glucose monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This AID system improves TIR compared to baseline by at least 10% after 4 weeks without any increase in TBR [ 15 , 29 , 38 ], and this finding has also been reported by other studies with longer follow-up periods of up to 1 year [ 30 , 31 , 34 , 36 , 39 ], which demonstrated a more remarkable improvement in TIR of up to 22% [ 35 , 37 ] without any significant change in BMI z -score [ 39 ]. Basically, the MiniMed™ 780G system allows a TIR of 75–80% to be reached [ 32 , 33 ]. It is worth noting that in all these studies, people with diabetes used rapid-acting insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This AID system improves TIR compared to baseline by at least 10% after 4 weeks without any increase in TBR [ 15 , 29 , 38 ], and this finding has also been reported by other studies with longer follow-up periods of up to 1 year [ 30 , 31 , 34 , 36 , 39 ], which demonstrated a more remarkable improvement in TIR of up to 22% [ 35 , 37 ] without any significant change in BMI z -score [ 39 ]. Basically, the MiniMed™ 780G system allows a TIR of 75–80% to be reached [ 32 , 33 ]. It is worth noting that in all these studies, people with diabetes used rapid-acting insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study evaluating the raw data for 4193 patient-days of 34 children using the AHCL system reported the following results for glucose control indicators: HbA1c 7.1 ± 0.9%, TIR 80.5 ± 7.8%, TAR1 14.5 ± 6.2%, TAR2 2.5 ± 2.2%, TBR1 2 ± 1.5%, TBR2 0.5 ± 0.8%, CV 33.1%, mean SG 136.7 ± 11.6 mg/dL, SD of mean glucose 45.5 mg/dL, and GMI 6.6%. No differences in the main CGM metrics were found between children older and younger than 9 years of age [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the development of type 1 diabetes before the age of 10 years results in a loss of 17.70 years of life (95%CI 14.50-20.40) for women and 14.20 years of life (12.10-18.20) for men [1,4]. These data may justify an increased focus on cardioprotection in people with early-onset T1D [5][6][7].…”
Section: Introductionmentioning
confidence: 96%
“…Multiple studies have shown that closed‐loop systems enable better glycemic control measured in glycated hemoglobin (HbA1c), TIR, hyperglycemia, hypoglycemia, lower variability, and improved quality of life 3–8 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Multiple studies have shown that closed-loop systems enable better glycemic control measured in glycated hemoglobin (HbA1c), TIR, hyperglycemia, hypoglycemia, lower variability, and improved quality of life. [3][4][5][6][7][8] One of the closed-loop systems is the Medtronic MiniMed 780G device. It features an advanced hybrid closed-loop (AHCL) algorithm that includes automatic delivery of basal insulin every 5 min, adjustable targets of 100 (5.50), 110 (6.10), and 120 (6.70) mg/dL (mmol/L), and automatic delivery of correction boluses every 5 min.…”
Section: Introductionmentioning
confidence: 99%